1992
DOI: 10.1104/pp.100.3.1377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brassinolide on Gene Expression in Elongating Soybean Epicotyls

Abstract: We have studied the effect of brassinolide (BR), a plant steroidal lactone, on the expression of auxin-regulated genes in soybean (Glycine max L. cv Williams 82) epicotyls. BR caused up to 4-fold increases in epicotyl length during extended assays at 10-M, in the absence of added auxin. Structurally related steroids failed to induce elongation or to alter the BR effect. Northern blot analysis, using sequences corresponding to auxin-regulated genes as probes, has shown that the molecular mechanism of BR-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0
4

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 33 publications
4
59
0
4
Order By: Relevance
“…As is the case with BAS1, CYP450-mediated C26-hydroxylation inactivates the insect hormones ecdysteroids, although the precise enzyme has not been identified (36)(37)(38). Though ecdysteroids are inactivated in a similar manner to BRs, these insect hormones do not induce BR responses in plants (39). Other insect juvenile hormones can be hydroxylated and presumably catabolized in a similar manner to ecdysone (40).…”
Section: Discussionmentioning
confidence: 98%
“…As is the case with BAS1, CYP450-mediated C26-hydroxylation inactivates the insect hormones ecdysteroids, although the precise enzyme has not been identified (36)(37)(38). Though ecdysteroids are inactivated in a similar manner to BRs, these insect hormones do not induce BR responses in plants (39). Other insect juvenile hormones can be hydroxylated and presumably catabolized in a similar manner to ecdysone (40).…”
Section: Discussionmentioning
confidence: 98%
“…Although BR may affect hypocotyl bending through modulation of polar auxin transport, it has also been well established that auxin and BR interact at the transcriptional level (Clouse et al, 1992;Goda et al, 2002;Mü ssig et al, 2002;Yin et al, 2002). Seventeen to 25% of the auxin-induced genes are also activated by BL in microarray analyses (Goda et al, 2004;Nemhauser et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…dicyclohexyl carbodiimide has revealed that elongation induced by BRs involve ATPases (Katsumi, 1985). Since other plant growth regulators such as GAs and auxins also promote cell elongation, the regulation of some auxin-regulated genes such as SAUR, GH1 and JCW was studied for response to BR (Clouse et al, 1992). This experiment showed that although GH1 and SAUR genes are upregulated by BR, the kinetics of regulation was very different when compared to their regulation by auxin.…”
Section: Discussionmentioning
confidence: 99%
“…They are highly effective in stimulating growth in young vegetative tissues. Brassinosteroids promoted elongation of mung bean, soybean, pea epicotyls, bean, sunflower and cucumber hypocotyls, Arabidopsis peduncles and Hordeum vulgare seedlings (Gregory, 1982;Clouse et al, 1992;Yu et al, 2004;Clouse, 2008 andKartal et al, 2009). Hypocotyl elongation of Packchoi (Brassica chinensis) by brassinosteroids was reported (Wang et al, 1993) and application to apical 3-mm region gave the best effect.…”
Section: Discussionmentioning
confidence: 99%